(3efXheI aj GdeLGR hGdESJYGQGJs - (3GdWHdGhj , efUhQ GdWHdGhj Hf SHW fGUQ GdOjf eMeO Hf SGde, SHW fGUQ GdOjf,J (B1014 (3g` s
(3ChdgG (B:s
(3jbhd SHW GdfGUQ GdWHdGhi efUhQ GdQGLi hGdLfGf GdKGhi GdMeO ddg Ydi GdJhajb dcGed GdHjGf hGdJMbjb s
(3BNQgG (B:s
(3gPG NJGe eG bUOfG fXeI hGdMeO ddg hdi GdfYeg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B15s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs